Experimental study of wall nucleation characteristics in flow boiling under subatmospheric pressures in a vertical square channel. (May 2019) - Colgan, Nathan; Bottini, Joseph L.; Ooi, Zhiee Jhia; Brooks, Caleb S.
Highlights: Subcooled flow boiling of water is studied under subatmospheric pressure. New data of bubble departure diameter and frequency is obtained. Existing modeling is benchmarked for use under subatmospheric pressures. Abstract: Experiments have been conducted in a vertical square channel to investigate wall nucleation characteristics in subcooled boiling flows under subatmospheric pressure. The objective of this work is to provide a unique dataset to evaluate the scalability of existing models of nucleation characteristics for flow boiling conditions below atmospheric pressure as the performance of these models has not been investigated under these conditions. The experimental data is presented as a parametric study of the effects of important dimensionless groups on nucleation characteristics, specifically boiling number, Jakob number, and density ratio. Bubble departure diameters and departure frequencies are measured and compared to existing models. Some existing models are shown to predict departure diameter well but mainly overpredict departure frequency at low pressure.